Update of Argentina’s Regulatory Policies on the Environmental Risk Assessment - Vesprini, Facundo; Whelan, Agustina Ines; Goberna, María Florencia; Murrone, Mariana Lucía; Barros, Gabriela Evangelina; Frankow, Andrés; Godoy, Perla; Lewi, Dalia Marcela (Frontiers in Bioengineering and Biotechnology, 2022)
The Environmental Risk Assessment (ERA) of Genetically Modified Crops (GM crops) in Argentina is carried out by the National Advisory Commission on Agricultural Biotechnology (CONABIA) and the Innovation and Biotechnology Coordination (CIyB). Both have a large experience with this assessment, since 1991, when CONABIA was created. The continuous support to biotechnology as a state policy and as part of the decision to encourage developers in the regulatory process has helped make progress in the revision of the regulations. The experience gained during the last 30 years and the worldwide scientific advances supported the bases to update the regulatory framework. Focusing on the biosafety strengthening and the improvement of the applicants experience in the GM crops evaluation process, during 2020 and 2021 the ERA went through a reviewing. Some important modifications were made, such as: i) the assessment of stacked GM crops with focus on the possible interactions between transgenes and the expression products, ii) the strengthening of the ERA taking into account the transportability of data and conclusions from the Confined Field Trials (CFT), iii) the adoption of Familiarity and History of Safe Use (HOSU) concepts on the risk assessment of the expression products, iv) the special considerations for the unintended effects of insertional sites and, v) as a post commercial release of GM crops, the Insect Resistance Management Plan (IRMP) was reformulated. These novel approaches enhance the ERA, they make it more efficient by applying the science criteria and the accumulated experience and scientific bibliography on the topic.